In the era of human capital : - Crawford, Richard (HarperBusiness, 1991)
In the era of human capital : the emergence of talent, intelligence, and knowledge as the worldwide economic force and what it means to managers and investors about: The Changing Economic and Business Enviroment; The Effect of the Knowledge Economy on Business and Management; The Effect of the Knowledge Economy on the Financial System and Investments...